Berkontemplasi dalam Era Digital: Peluang Meningkatkan Spiritualitas Generasi Z - Tesha Widyanari Anggraeni Rumpoko (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2026)
Generation Z is a generation born and raised in the digital era, making technology an inseparable part of their daily lives. While technological advancements provide easier access to information and spiritual resources, they also present challenges such as digital distractions, digital addiction, diminished capacity for reflection, and increasing psychological and spiritual pressures. This article aims to examine contemplative practices as a means of fostering the spirituality of Generation Z amid the dynamics of the digital age. The study employs a literature review method by analyzing various sources on the characteristics of Generation Z, the impact of digital technology on spiritual life, and the concept of contemplation within the Christian tradition. The findings indicate that contemplation can serve as a space for cultivating silence, self-awareness, faith reflection, and a deeper relationship with God. Contemplative practices may be expressed through creative prayer, the Examen of Consciousness, digital detox, reflection through art and physical activity, social service, as well as the use of digital applications and online communities that support spiritual growth. When technology is used wisely, the digital era can also become an opportunity to cultivate a reflective, authentic, and contextually relevant spirituality for Generation Z.